Global challenges in aging: insights from comparative biology and one health - Ottinger, Mary Ann; Grace, Jacquelyn K.; Maness, Terri J. (Frontiers in Toxicology, 2024)
The well-being of wildlife populations, ecosystem health, and human health are interlinked, and preserving wildlife is crucial for sustaining healthy ecosystems. Wildlife numbers, and in particular avian populations, have steeply declined over the past century, associated with anthropogenic factors originating from industry, urbanization, changing land use, habitat loss, pollution, emerging diseases, and climate change. All these factors combine to exert increasing stress and impair health for both humans and wildlife, with diminished metabolic, immune, and reproductive function, deteriorating overall health, and reduced longevity. The "toxic aging coin" suggests that these stressors may have dual impacts on aging -they can accelerate the aging process, and older individuals may struggle to cope with pollutants compared to younger ones. These responses are reflected in the health and productivity of individuals, and at a larger scale, the health and ability of populations to withstand disturbances. To understand the potential risk to health over the lifespan, it is important to articulate some of these global challenges and consider both their impacts on aging populations and on the aging process. In this review, we use the toxic aging coin and One Health conceptual frameworks to examine the interconnected health of humans, wildlife, and ecosystems. This exploration aims to develop proactive approaches for optimizing wildlife and human health.